Efficient Subsidization of Human Capital Accumulation with Overlapping Generations and Endogenous Growth - Christoph Braun; Wolfram F. Richter (Verein für Socialpolitik, 2010)
This paper studies second best policies for education, saving, and labour in an OLG model in which endogenous growth results from human capital accumulation. Government expenditures have to be financed by linear instruments so that growth equilibria are inefficient. The inefficiency is exacerbated if selfish individuals externalize the positive effect of education on descendents' productivity. It is shown to be second best to subsidize education even relative to the first best if the elasticity of the human capital investment function is strictly increasing.
Keywords: H21; I28; J24; 330; OLG model; endogenous growth; endogenous labour; education; and saving; intergenerational externalities; optimal taxation